Analysis of Interests and Learning Outcomes of Elementary School Natural Sciences Through Contextual Approach: Analisis Minat dan Hasil Belajar Ilmu Pengetahuan Alam Sekolah Dasar Melalui Pendekatan Kontekstual - Muhammad Baharudin Adenan; Nur Efendi (Academia Open, 2021)
This study discusses the analysis of interest and learning outcomes of elementary school natural science through a contextual approach. With this, the researcher found several problems that need to be researched. The problem is about how interest in learning natural science in elementary school through a contextual approach and how learning outcomes in elementary school natural science through a contextual approach. This problem makes the researcher take a qualitative descriptive research approach using the literature study method. Sources of data obtained from journals, articles and other previous research. Sources of data taken in the study must be at least the last five years. The results obtained from the research are that students have increased interest in learning and learning outcomes of natural science using a contextual approach. These results make the researcher conclude that the contextual approach can affect the interest and learning outcomes of students in natural science material.